Robotics in Construction of Concrete and Masonry Structures - Nyamsuren, Anudari; Anudari Nyamsuren (České vysoké učení technické v Praze, 2019)
This research work investigates the current state of the art of robotics in the construction industry as well as in concrete and masonry field. To fully understand the possibilities of implementation of robotics in construction industry, the basic principles of robotics are discussed at first. The general overview of robotics: definitions, brief history, robot's main parts, and recent developments in different fields are covered. The main part of the thesis is focused on the robotics application in construction industry. The main reasons for future robotization of the industry, the advantages and challenges facing the robotics application in construction industry are discussed. Few examples of robots are chosen for review to show the wide range of possible application. At last, the further developments of robotics in construction are mentioned.

This research work investigates the current state of the art of robotics in the construction industry as well as in concrete and masonry field. To fully understand the possibilities of implementation of robotics in construction industry, the basic principles of robotics are discussed at first. The general overview of robotics: definitions, brief history, robot's main parts, and recent developments in different fields are covered. The main part of the thesis is focused on the robotics application in construction industry. The main reasons for future robotization of the industry, the advantages and challenges facing the robotics application in construction industry are discussed. Few examples of robots are chosen for review to show the wide range of possible application. At last, the further developments of robotics in construction are mentioned.
Robotics in Construction of Concrete and Masonry Structures
Keywords: robotics; building automation; construction robots; concrete structures; masonry structures; robotics; building automation; construction robots; concrete structures; masonry structures